Using the wisdom of crowds in sports: how performance analysis in football can benefit from the information enclosed in betting odds - Wunderlich, F. (International Journal of Performance Analysis in Sport, 2025)
Betting odds have proven to contain highly accurate information on football matches, which researchers have used to study sports integrity, human behaviour, economic theories or forecasting, but widely neglected in performance analysis to date. The paper intends to stimulate changing this as betting odds contain a wealth of information usable to control for the inherent playing strength of teams as a situational variable and thus to better distinguish between strength, performance and success. Crowd wisdom and market efficiency are discussed as theoretical concepts driving the accuracy of betting odds. Moreover, based on a dataset of nearly 100 000 matches from 17 seasons in 17 European men`s football leagues, this study demonstrates that odds outperform methods related to points or goals in predicting the match winner as well as the anticipated number of goals by both teams. The code used in this study is made available to public in order to provide performance analysts with tools to extract information from odds. Finally, examples on how to benefit from betting odds in performance analysis are highlighted. Results of these use cases suggest that the relationship between performance and success can indeed be confounded by team strength, emphasising the need for further investigation.